Loneliness in Adolescents with Attention Deficit Hyperactivity Disorder (ADHD) - I Made Wedastra; Yunias Setiawati (Faculty of Medicine, Universitas Airlangga, 2024)
Introduction: Attention deficit hyperactivity disorder is a disorder of children’s growth and development with neurodevelopmental disorders characterized by symptoms of inattention, hyperactivity, and impulsivity. ADHD in children can persist into adolescence in about 2.6% of the general population. About more than half of people with ADHD experience loneliness, a condition that is often not reported by patients but is evident in the negative emotions and behaviors they display. To explain the risk factors and impact of loneliness in adolescents with ADHD. Methods: Literature review. Results: The use of gadgets in today’s digital era increases the risk of increasing internet usage so that more contact is made online, which causes obstacles for adolescents in fostering social relationships and an increased risk of loneliness. Adolescents with ADHD have a negative assessment of themselves; they feel useless, lack confidence, and lack intelligence when compared to their peers. Economically, low-income family conditions and inappropriate parenting increase the risk of loneliness in ADHD adolescents. Adequate treatment will cause it to develop into other mental disorders such as anxiety, depression, defiant attitude disorder, and adolescent behavior disorder. Conclusions: Adolescents with ADHD are prone to experiencing loneliness. Parenting problems, family socioeconomics, past trauma, bullying, and several internal factors such as low self-confidence, insecurity, low adaptability, and lack of emotional control can cause loneliness. Keywords: ADHD, Adolescents, Loneliness, Mental Health, Psychological Well-Being